Acupuncture treatment of restless legs syndrome: a randomized clinical controlled study protocol based on PET-CT and fMRI - Tang, Lin; Zhao, Na; Gao, Xiaolin; Li, Jinjin; Yu, Xintong; Liang, Ruilong; Xie, Chen; Li, Lutong; Wang, Qianqian; Yang, Wenjia (Frontiers in Psychiatry, 2024)
IntroductionRestless legs syndrome (RLS) is a sensorimotor disorder of the nervous system that is mainly characterized by nighttime leg discomfort and can be accompanied by significant anxiety, depression, and other mood disorders. RLS seriously affects the quality of life. Clinical studies have confirmed that acupuncture can alleviate the clinical symptoms of RLS. This randomized controlled trial (RCT) aims to investigate the efficacy of acupuncture in the treatment of RLS and further explore the central response mechanism of acupuncture in the treatment of RLS.Methods and analysisIn this RCT, a total of 124 eligible patients in Shanghai will be randomly assigned to one of the following two groups: treatment group (acupuncture) and control group (sham acupuncture). Treatment will be given three times per week for 4 consecutive weeks. The primary outcome is the International Restless Legs severity rating scale (IRLSS). The secondary outcomes are the RLS-Quality of Life (RLSQoL), the Insomnia Severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), the Hamilton Depression Scale (HAMD), and the Hamilton Anxiety Scale (HAMA). The objective evaluation tools will be polysomnography, positron emission tomography–computed tomography (PET-CT), and functional magnetic resonance imaging (fMRI) of the brain. All adverse effects will be assessed by the Treatment Emergent Symptom Scale. Outcomes will be evaluated at baseline (1 week before the first intervention), during the intervention (the second week of the intervention), after the intervention (at the end of the intervention), at 1-month follow-up, and at 3-month follow-up.Ethics and disseminationThe trial has been approved by the Ethics Committee of Yueyang Hospital of Integrated Traditional Chinese and Western Medicine (no. 2022-061). Written informed consent will be obtained from all participants. The results of this study will be published in peer-reviewed journals or presented at academic conferences.Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR2000037287.